O uso do cigarro eletrônico e suas consequências ao organismo: doenças e toxicidade - Silva, Camila Castilhos Bernardo da (My University, 2025)
Given the current scenario, it is known that smoking is a major global problem that has increasingly increased over the years. This is because not only the conventional cigarette is found in society, but also the electronic cigarette, which is a device that does not generate combustion but rather vaporization in which it contains aerosols. It is no longer a secret for anyone that adverse symptoms are one of the most visible manifestations of electronic cigarette (EC) users and in turn, it is believed that with frequent use it can be causing many dysfunctions in the body. Therefore, EC exposes the smoker's body to various chemicals such as nicotine, flavorings and propylene glycol, which are exposed during evaporation. The main damages caused are Lung Injury Associated with Electronic Cigarette Use (EVALI), cardiovascular injuries, oxidative stress, cancer, among others. It is understood that previously the marketing done for this device was to stop smoking, today, after some studies, results have been obtained that say the opposite, showing that electronic cigarettes are also an agent tha causes risks to the user's health. Even though it is a recent device, it is already possible to demonstrate through numerous scientific studies that its use is harmful and that the consequences are for the user and for the people who live with it. Due to the increased use of this device, this topic has been the subject of studies in many countries to better understand its mechanisms. [resumo fornecido pelo autor]
Em face do cenário atual, sabe-se que o tabagismo é um grande problema mundial na qual cada vez mais vem aumentando com o passar dos anos. Isso porque, não somente o cigarro convencional é encontrado na sociedade, mas também, o cigarro eletrônico que é um dispositivo que não gera combustão e sim vaporização na qual são os aerossóis. Já não é mais segredo para ninguém que os sintomas respiratórios é uma das manifestações mais visíveis dos usuários de cigarro eletrônico (CE) e por sua vez, acredita-se que com o uso frequente possa estar causando demais disfunções no corpo. Portanto, o CE expõe o organismo do fumante a diversos produtos químicos como nicotina, aromatizantes, propilenoglicol, que expostos no ato da evaporação. Já os principais danos causados são Lesão Pulmonar Associada ao Uso do Cigarro Eletrônico (EVALI), lesões cardiovasculares, estresse oxidativo, câncer entre outras. Compreende-se que anteriormente o marketing feito para este dispositivo era para cessar o tabagismo, todavia, após alguns estudos já se obtêm resultados que dizem ao contrário, apresentando que o cigarro eletrônico também é um agente causador de riscos à saúde do usuário. Mesmo sendo um dispositivo recente, já é possível evidenciar através de inúmeros estudos científicos que seu uso nocivo e que as consequências são para o usuário e para as próprias pessoas que convivem com ele. Devido ao aumento do uso desse dispositivo, esse tema tem sido alvo de estudos em muitos países a fim compreender melhor os seus mecanismos. [resumo fornecido pelo autor]
Keywords: Cigarros eletrônicos; Testes de toxicidade; Fumo - Vício - Aspectos da saúde